Ragam dan Perkembangan Penegakan Hukum di Indonesia Pasca Reformasi - Bagus, Moh (Al-Jinayah : Jurnal Hukum Pidana Islam, 2022)
One of the important principles in a democratic country is the creation of independent and impartial law enforcement. This principle must always be maintained as an effort to protect human rights and to create and place law as the supreme commander of the state. This article on the variety and development of law enforcement in Indonesia will try to provide an overview and portrait of law enforcement in Indonesia that has been running so far. In order to provide a repertoire of legal improvements in Indonesia, the author will provide limitations on law enforcement, especially since the reformation to date. In this study, the authors used normative legal research methods with statutory, conceptual and case approaches. The results of the study state that various legal products in Indonesia are always present in order to complement and improve the components of law enforcement in Indonesia. In addition, the presence of the Constitutional Court as a style of constitutional interpreter also provides a new color through various kinds of decisions.